Personality, Gender, Culture, and Entrepreneurial Intentions of Undergraduate Student: Binary Logistic Regression - Bambang Mardisetosa; Khusaini Khusaini; Gumelar Widia Asmoro (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2020)
In the last two decades, empirical studies on entrepreneurship had been increasing, especially the object of study of student entrepreneurial intention. The objective of this study was to examine the empirical evidence about significant factors and the most dominant factor (having the highest rank) influencing entrepreneurial intention of Islamic Shekh-Yusuf University students. This study used a descriptive quantitative approach that was a binary logistic regression analysis model with a sample of 382 respondents from a population of 4.058 students. Data obtained using a questionnaire tested for validity and reliability. Measurement scale used a Likert scale, and the distribution of questionnaire was accidental sampling technique. Based on binary logistic regression analysis, it showed that personality and situational significantly influenced students entreprenurial intentions, while culture and gender were not significant. The contribution of this research was as input to the university about the importance of developing students' entrepreneurial interets and talents so that graduates could contribute to reducing unemployment.